DENSITY ZOOXANTHELLA BASED ON THE LIFE FORM OF CORAL ON MARAK ISLAND WEST SUMATERA PROVINCE - Lieng, Lieng; Efriyeldi, Efriyeldi; Thamrin, Thamrin (Asian Journal of Aquatic Sciences, 2020)
This study aims to determine differences in zooxanthella density based on the life forms of coral Acropora Branching, Submassive Acropora, Branching, Foliose, Heliopora and comparing zooxanthella densities between the forms of coral form. This study was conducted in January-February 2020 on Marak Island, Nagari Sungai Pinang, West Sumatera Province. Zooxanthella density was calculated at the Marine Biology Laboratory, Department of Marine Sciences, University of Riau. The survey methode was used in this study, where the data collected was primary data. Coral Sampling was done by free collection using the SCUBA (Self Contained Underwater Breathing Apparatus). The result of study in the waters of Marak Island, West Sumatera on Acropora Branching corals were in the range of 0.004-0.13×106 cells/cm2. Acropora Submassive range of 2.95- 3.56×106 cells/cm2. Branching range of 2.41-2.59×106 cells/cm2. Foliose range of 0.44-1.09×106 cell/cm2. Heliopora range of 1.30-1.59×106 cell/cm2. The highest zooxanthella density was in Submassive Acropora and the lowest in Acropora Branching corals due to different forms of growth and temperature influences. Different forms of coral growth affect the zooxanthella density on a coral and the success of coral growth depends on the zooxanthella density and the size of the corallite of each coral life form.